Employing organizational symmetry in achieving sustainable strategic performance)) : دراسة استطلاعية لآراء عينة من العاملين في شركتي البيبسي كولا وشركة كوكاكولا. - kidhem Hussein alsharifi, Ali (Iraqi Journal for Administrative Sciences, 2024)
Nowadays, well-performing organizations can be counted as the ones that are able to invest all their resources to adapt to continuous changes to achieve the best possible performance. Therefore, the current research sheds light on two basic variables (organizational symmetry and sustainable strategic performance) by determining the level of correlation and impact of organizational symmetry with its dimensions (loyalty, affiliation, similarity) on sustainable strategic performance in its dimensions (financial perspective, customer perspective, internal processes, innovation and organizational learning. Measuring the level of their application to the sample under study, and in order to achieve the goal of the research, the research started from a problem expressed in a number of intellectual questions. Is there an employment of organizational symmetry in thought and behavior commensurate with the development in sustainable strategic performance? The questionnaire was used as a tool for data collection. A intended sample consisted of (52) individuals from different levels represented by (managers, heads of departments, directors of divisions and units and some employees) in the two companies (Pepsi-Cola Company and Coca-Cola Company) distributed to them, and in order to prove the validity of the hypotheses, the statistical program (SPSS) and the test (T) were used. ) And (F), and the research was launched with a number of conclusions, the most prominent of which is the existence of a correlation and influence between organizational symmetry and sustainable strategic performance, which has become a source of global concern. All competing organizations seek it. As for the most important recommendations, the need to pay attention to organizational symmetry, as it represents a positive emotional behavior and feeling and an urgent humanitarian need to regulate the relationship between the workers themselves and between the workers and the organization.